Gambaran Kepercayaan Masyarakat Pesisir saat Masa Kehamilan hingga Masa Nifas di Wilayah Batang Kilat Kecamatan Medan Labuhan Tahun 2023 - Nurhayati, Nurhayati; Lubis, Amru Prabowo; Prasetyo, Agung; Purba, Fadila Syahrani; Puspitasari, Inda; Purba, Nurul Fitriani; Keysah, Shindu; Maimuna, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Various cultures related to pregnancy and postpartum still exist in society with various forms of prohibitions and behaviors that must be avoided by mothers during pregnancy and postpartum. Batang Kilat Coastal Area in Medan Labuhan District is a modern coastal area, so research on cultural practices related to pregnancy and postpartum needs to be conducted there. The purpose of this research is to explore beliefs and cultural practices related to pregnancy and postpartum in the Batang Kilat area. This research uses a qualitative approach with a case study and data collection method through in-depth interviews. The participants in this research are pregnant women and postpartum women, with a total of seven participants. The results of the research show five main themes, namely views on examination and care during pregnancy, views on birth attendants, views on food taboos and behaviors during pregnancy, views on behavior during postpartum, and family support in postpartum care.